2018
DOI: 10.7150/jca.25082
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin enhances VEGFR1 expression through up-regulation of ETS-1 transcription factor

Abstract: Angiogenesis is required for tumor growth. Dihydroartemisinin (DHA), a the effective anti-malarial derivative of artemisinin, demonstrated potent anti-angiogenic activities that closely related to the regulation of vascular endothelial growth factor (VEGF) signaling cascade. VEGF receptor 1 (VEGFR1), a receptor in endothelial cells (ECs), coordinately regulate angiogenic activity triggered by ligand-receptor binding. Here we aimed to explore the effects of DHA on VEGFR1 expression in ECs. We found that DHA sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Youyou Tu awarded the Nobel Prize in physiology or medicine in 2015 for her great contribution to discover the antimalarial effect of artemisinin. Dihydroartemisinin (DHA), one of the derivatives of artemisinin, was found to own anticancer effects on numerous kinds of cancers [9,10,32]. The study of the anticancer effect of DHA on esophageal cancer is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Youyou Tu awarded the Nobel Prize in physiology or medicine in 2015 for her great contribution to discover the antimalarial effect of artemisinin. Dihydroartemisinin (DHA), one of the derivatives of artemisinin, was found to own anticancer effects on numerous kinds of cancers [9,10,32]. The study of the anticancer effect of DHA on esophageal cancer is limited.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that DHA induces autophagy in human umbilical vein endothelial cells by inhibiting Akt and mTOR signaling pathways, thereby inhibiting their ability to generate blood vessels in vitro (66). In addition, DHA also inhibits angiogenesis by increasing the expression of VEFGR1, a deceptive receptor of VEGF, to block the binding of VEGF and VEFGR2 (67). Li et al find that DHA inhibits esophageal cancer growth and metastasis by inhibiting the phosphorylation of p65 and reducing the activity of HIF-1a and VEGF (40).…”
Section: Inhibition Of Tumor Metastasismentioning
confidence: 99%
“…Most importantly, our findings suggest that REST-driven modulation of tumor vasculature may contribute to the increased incidence of metastasis and poor survival in patients with SHH-α and SHH-β MBs. ETS1 is a transcription factor and is a known regulator of angiogenic growth factors such as VEGFR1 [44,59,45]. Given the strong correlative parallels in REST and ETS1/CD31/VEGFR1 expression between SHH-MBs and Group 4 MBs, similar mechanisms could be operational in these two subgroups of MBs.…”
Section: Discussionmentioning
confidence: 99%
“…6C,D). The above findings taken in conjunction with VEGFR1 being a known ETS1 target gene, led us to assess whether REST-dependent increase in VEGFR1 expression in DAOY-R cells is mediated by ETS1 [44,45]. Knockdown experiments showed that reduction of ETS1 in DAOY-R cells using two different shRNA-ETS1 constructs did indeed result in a decrease in VEGFR1 levels in these cells (Fig.…”
Section: Rest Elevation Drives Ets1-dependent Increase In Vegfr1 Expressionmentioning
confidence: 99%